Cernunnos in Slovenia? - Šašel Kos, Marjeta (Arheološki vestnik, 2010)
A tombstone with seven busts (second or early third centur y AD), which was most probably discovered at Črnomelj in Bela Krajina, displays poorly visible side reliefs. On the right side a human figure with horns and hooves and a dog trying to bite his thigh are depicted. On the left a horseman holding a spear is represented in the upper field, while in the lower part three figures are depicted, of whom the middle one is a woman; a man with a spear is standing in front of her.Peter Petru explained the badly preserved figures as scenes referring to the Celtic god Cernunnos and to hu-man sacrifice performed in his honour. However, these depictions would better correspond to the episodes from the myth of Actaeon